2017
DOI: 10.1073/pnas.1701170114
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transport of tropospheric aerosol into the stratosphere via the Asian summer monsoon anticyclone

Abstract: An enhanced aerosol layer near the tropopause over Asia during the June-September period of the Asian summer monsoon (ASM) was recently identified using satellite observations. Its sources and climate impact are presently not well-characterized. To improve understanding of this phenomenon, we made in situ aerosol measurements during summer 2015 from Kunming, China, then followed with a modeling study to assess the global significance. The in situ measurements revealed a robust enhancement in aerosol concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 40 publications
7
153
0
Order By: Relevance
“…Whether these differences result from model design, incorrect boundary conditions (e.g. underestimated anthropogenic (Yu et al, 2017) or volcanic (Bandoro et al, 2018) aerosol contributions), or missing chemistry remains an open question.…”
Section: Comparison Of Stratospheric Spatial and Partial Column Ozonementioning
confidence: 99%
“…Whether these differences result from model design, incorrect boundary conditions (e.g. underestimated anthropogenic (Yu et al, 2017) or volcanic (Bandoro et al, 2018) aerosol contributions), or missing chemistry remains an open question.…”
Section: Comparison Of Stratospheric Spatial and Partial Column Ozonementioning
confidence: 99%
“…Vernier et al (2018) and Yu et al (2017) provided additional in situ verification of the ATAL from recent balloon launches in India and Saudi Arabia, and from China, respectively. The presence of an ATAL suggests that the ASM may provide a conduit for aerosols, and/or precursor gases, to reach and be dispersed in the UTLS (Neely et al, 2014;Yu et al, 2017). In addition, the proximity of ATAL aerosols to ice clouds in the ASM anticyclone (Vernier et al, 2018) indicates the potential for ATAL aerosols to alter cloud optical properties (Fadnavis et al, 2013(Fadnavis et al, , 2017Li et al, 2005), which could impact regional climate.…”
Section: 1029/2019jd031506mentioning
confidence: 99%
“…They detected relatively high number concentrations (0.7-0.8 cm −3 ) of submicron-sized aerosols (0.3-1.2 μm in diameter) present near the tropopause region and inside the ASM region and were suggested to be induced by the deep convection over the TP. Later, in 2015, by analyzing measurements from the Portable Optical Particle Counter (POPS) (Gao et al 2016) in Kunming (25.01°N, 102.65°E; 1889 m ASL, as shown in figure 1), Yu et al (2017) confirmed the existence of a robust enhanced aerosol layer that extends up to 2 km above the tropopause. Both studies have indeed provided valuable observations about the aerosol layer during the ASM period; nevertheless, as specified later, in section 4, they also have their own limitations.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies showed that the ASM may transport tropospheric air into the stratosphere effectively by creating a dome or 'bubble' of tropospheric air above the zonal mean tropopause (Randel and Park 2006, Park et al 2007, Pan et al 2016. It is further noted that the ASM coupled with deep convection uplifting may serve as a more efficient chimney, venting tropospheric aerosols up to the UTLS, thereby significantly influencing the high-altitude aerosol properties (Li et al 2005, Randel et al 2010, Vernier et al 2015, Yu et al 2015, 2017.…”
Section: Introductionmentioning
confidence: 99%